Factors Influencing Behavior of Reducing Exposure to Endocrine Disrupting Chemicals in Breastfeeding Mothers - Sun Hyang Kim; Eun Young Jun (Korean Society of Women Health Nursing, 2018)
PURPOSE: To investigate factors that affect behaviors of reducing exposure to endocrine disrupting chemicals (EDCs) in breastfeeding mothers. METHODS: Subjects were 166 breastfeeding mothers who were recruited from January 25 to April 15, 2018. The questionnaire consisted of items associated with behaviors of reducing exposure to EDCs, attitude to behaviors of reducing exposure, subject norms of behavior of reducing exposure, and perceived behavior control. Data were analyzed by t-test, ANOVA, Pearson correlations, and stepwise multiple regression. RESULTS: Factors influencing behaviors of reducing the exposure to EDCs were attitude toward behaviors of reducing exposure, perceived barrier, and period of lactation. The more positive the attitude toward behaviors of reducing exposure was, the lower the perceived barrier. The longer the feeding period, the higher the behaviors of reducing the exposure to EDCs. CONCLUSION: To enhance behaviors of reducing the exposure to EDCs, it is necessary to develop a positive educational program in breastfeeding department to improve attitude toward behaviors of reducing the exposure to EDCs, decrease perceived barrier, and increase the breastfeeding period.